If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(-1x + 2) = -49 Reorder the terms: 7(2 + -1x) = -49 (2 * 7 + -1x * 7) = -49 (14 + -7x) = -49 Solving 14 + -7x = -49 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + -7x = -49 + -14 Combine like terms: 14 + -14 = 0 0 + -7x = -49 + -14 -7x = -49 + -14 Combine like terms: -49 + -14 = -63 -7x = -63 Divide each side by '-7'. x = 9 Simplifying x = 9
| r-19=-39 | | 2x+7+4x=-5 | | 6x-16=48 | | 6x+1+3x=46 | | (2x+4)(3x+5)=0 | | 3x+=30 | | 5x-3+2x=-80 | | 7=3x-x+3 | | -14=-3x+7x+10 | | 20-4x=-6x+12 | | (n-2)180=60 | | -4+4x+6x=-54 | | 7x+6+6x=110 | | t/-12=-4/15 | | -2*-4=5+8 | | -6+6x-4x=16 | | x^2-4ax-2=0 | | -5x+7+2x=-8 | | 1=5x+3x-7 | | 1=p+12 | | 3*-2=5*4-26 | | -21n=483 | | 3sinx+4cosx^2=0 | | r+2=15 | | -3*-2=x+2 | | 2u+10=26 | | (2x-5)(3x+4)= | | 5x(63-16)= | | m^3-6=0 | | (4w-8)(w+3)=0 | | -2in(x)+in(y)=in(6) | | 6x^2-11x-13=5(x^2-1)+3 |